Selflessness, Depression, and Neuroticism: An Interactionist Perspective on the Effects of Self-Transcendence, Perspective-Taking, and Materialism - Wegemer, Christopher M. (Frontiers in Psychology, 2020)
Dominant theories of depression position self-concept as a central determinant of psychological functioning, but the relationship between the structure of self-concept and depression has not been extensively explored. The present study investigates the relationship between the structure of the self and psychopathological outcomes (depressive symptoms and neuroticism) with two methodological approaches. Using an established framework that draws insight from Buddhist psychology, the structure of the self is conceptualized in terms of selflessness and self-centeredness. Specifically, selflessness is construed as a multidimensional concept characterized by interdependence, outsider phenomenology, and impermanence. The three dimensions of the self were assessed at age 26 with inventories of self-transcendence, perspective-taking, and materialism, respectively (N = 814). First, a variable-centered approach was used to investigate potential interactions between the dimensions of selflessness. Self-transcendence negatively predicted depressive symptoms and neuroticism, whereas perspective-taking and materialism were positively associated with the outcomes. Self-transcendence moderated the relationship between perspective-taking and depressive symptoms. Perspective-taking was not statistically related to depressive symptoms for participants who exhibited higher levels of self-transcendence. The results clarify ambiguous associations between perspective-taking and depression found in previous research. Second, person-centered analyses were used to identify five profiles of self-structure: (1) Selfless, (2) Selfless Materialist, (3) Interdependent Insider, (4) Self-centered Non-materialist, and (5) Self-centered. As hypothesized, the Selfless cluster was associated with low levels of depressive symptoms and neuroticism, whereas the Self-centered cluster was associated with high levels. The profiles demonstrate the manifestation of several combinations of features of the self, which contributes to overall understanding of selflessness by complicating the traditional dichotomy between selflessness and self-centeredness.